Intraparticle phosphorus diffusion in a drinking water treatment residual at room temperature - El-Shall, Hassan E.; Harris, Willie G.; O'Connor, George A.; Obreza, Thomas A.; Makris, Konstantinos C. (My University, 2004)
Phosphorus (P) has been recognized as one of the major limiting nutrients that are responsible for eutrophication of surface waters, worldwide. Efforts have been concentrated on reducing P loads reaching water bodies, via surface runoff and/or leaching through a soil profile. Use of drinking water treatment residuals (WTRs) is an emerging cost-effective practice to reduce soluble P in poorly P-sorbing soils or systems high in P. Literature suggests that WTRs have huge P sorption capacities. We hypothesized that P sorption would be limited by diffusional constraints imposed by the WTR particles. Selected chemical and physical (specific surface area, particle size distribution) characteristics of an iron-based WTR were measured. Sorption P isotherms at room temperature were constructed, and sorption kinetics were monitored. An intraparticle diffusion model was utilized to fit the kinetic data. Results showed that the WTR dramatically reduced soluble P, showing nonequilibrium characteristics, even after 80 d of reaction. Specific surface area (SSA) measured with CO2 gas was significantly greater than the traditional BET–N2 value (28 versus 3.5 m2 g−1), suggesting that a large amount of internal surfaces might be present in the WTR. The intraparticle P diffusion model was modified to include the wide particle size distribution of the WTR. The intraparticle diffusion model fitted the data well (r2=0.83). We calculated a maximum apparent P diffusion coefficient value of 4×10−15 cm2 s−1, which agrees with published values for intraparticle diffusion in microporous sorbents. This work may be useful for predicting long-term sorption characteristics of WTRs, since WTRs have been suggested as potential long-term immobilizers of sorbed P in P-sensitive ecosystems.
Keywords: Phosphorus; Intraparticle diffusion; Sorption capacity; Long-term immobilization